Analysis on Public-Based Water Source Conservation (A Case Study in Insana Region, Timor Tengah Utara) - Emanuel M.Y Hanoe; Bagyo Yanuwiadi; Rudy Sulistyono (Indonesian Journal of Environment and Sustainable Development, 2019)
Conservation refers to effort to explore and use natural resources wisely in order to maintain their value, quality and sustainability. Spring, an example of ground water resource, becomes major source of water for the society. Purpose of water source conservation is to maintain characteristics and function of water source, preserve environment around the water source and make sure there is ample supply of clean water now and in the future. Important aspect in water source management is participation from the society, public and private institution in water source conservation program. Efforts and appropriate water management systems to conserve water-use based on resources are more focused on determining the required components from upstream to downstream so that community-based water conservation concepts can be achieved well for sustainability for the benefit of society and environmental goals. The objectives of the study were to analyze 1) public participation, and 2) strategies for public-based water source conservation in Insana region. The study was descriptive quantitative study. Arstein ladder was used to identify public participation and SWOT analysis was used to develop the strategy. The results of the analysis show that based on the Arstein ladder, the public participation was categorized as informing. Furthermore, based on the SWOT analysis, the water source conservation strategies were conducting conservation program, minimizing social conflict, establishing regulations on conservation areas and water source preservation, conducting human resource development program for the locals.Keywords: Conservation, Insana Region, Public Participation, Water Source